(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
Avian influenza poses a significant threat to poultry farms, leading to substantial economic losses and public health concerns. Effective control strategies, including vaccination and treatment, are essential to mitigate the spread of the disease. This study aims to develop a mathematical model to understand the dynamics of avian influenza in poultry farms and evaluate the impact of vaccination and treatment interventions. A compartmental model was constructed to represent the transmission dynamics of avian influenza among poultry populations. The model includes compartments for susceptible, exposed, infected, and recovered birds, with additional compartments for vaccinated and treated birds. Differential equations were used to describe the transitions between compartments. Parameters were estimated from existing literature and field data. The model was analyzed using numerical simulations to assess the effectiveness of different intervention strategies. The model simulations indicated that a combination of vaccination and treatment significantly reduces the prevalence of avian influenza in poultry farms. Vaccination alone was effective in lowering the infection rate, but the addition of treatment further decreased the number of infected birds. Sensitivity analysis revealed that the timing and coverage of vaccination are critical factors in controlling the outbreak. Early and widespread vaccination, coupled with prompt treatment of infected birds, was found to be the most effective strategy. The mathematical model provides valuable insights into the dynamics of avian influenza and the impact of control measures in poultry farms. The findings suggest that integrated strategies involving both vaccination and treatment are essential for effective disease management. Policymakers and farm managers should consider these strategies to enhance the resilience of poultry farms against avian influenza outbreaks.